Pembuatan Kontrak Hukum: Teori, Teknik, Dan Kesalahan Yang Harus Dihindari - Anindya Larasati Patrianegara (JURNAL ILMIAH NUSANTARA, 2024)
The creation of legal contracts is an integral part of every business transaction and legal relationship between the parties. A valid and effective contract requires an understanding of the basic principles and proper techniques in its preparation, so that there are no misinterpretations that can lead to disputes. The principles of consensualism, freedom of contract, good faith, and clarity of rights and obligations are important foundations in ensuring that contracts have legal validity. In addition, the use of clear language, regulations on dispute resolution, and clauses regarding sanctions or force majeure are also techniques that must be applied to avoid mistakes that can harm the parties involved. Common mistakes in making contracts include unclear clauses, inconsistencies with applicable laws, and lack of clarity regarding the rights and obligations of the parties. Therefore, it is very important to pay attention to every aspect in the preparation of the contract so that the contract made is valid, binding, and can be implemented in accordance with applicable laws. In an effort to minimize legal risks, it is advisable to involve legal experts in the creation of contracts as a preventive measure to ensure a valid and effective contract.